The Influence of Digital Marketing and Brand Trust on Customer Loyalty Through Customer Satisfaction of Food and Beverage Companies - Andriana, Ririn (LPPPIPublishing, 2025)
This study aims to analyze the effect of digital marketing and brand trust on customer loyalty, with customer satisfaction serving as a mediating variable, within the context of food and beverage companies in East Java. In addition, the research seeks to examine the strategic role of customer satisfaction in strengthening the relationships among the key variables. A quantitative approach was employed, utilizing Structural Equation Modeling (SEM) as the method for data analysis. Data were collected through a survey questionnaire distributed to customers of food and beverage companies in East Java, using a purposive sampling technique. The findings reveal that both digital marketing and brand trust have a significant positive influence on customer loyalty. Furthermore, customer satisfaction was found to mediate the relationship between digital marketing and brand trust on customer loyalty, suggesting that customer satisfaction plays a crucial role in enhancing customer loyalty. This research provides valuable contributions to the existing literature by expanding the understanding of how digital marketing, brand trust, and customer satisfaction interact to influence customer loyalty, particularly in the food and beverage industry. Additionally, the findings offer practical implications for businesses in designing more effective customer-oriented digital marketing strategies. By focusing on customer satisfaction, companies can enhance their competitive advantage and foster long-term customer loyalty, which is essential for sustaining growth in an increasingly competitive market.